Qualifier la gestion de l’eau, se positionner par rapport au conflit : les cas de l’usine de dessalement dans la bande de Gaza et du canal entre la mer Rouge et la mer Morte - Klervi Fustec (Développement Durable et Territoires)
We can consider large infrastructure projects as part of politicization processes, or, conversely, as a technical issue. This is the case of the project of desalination plant in the Gaza Strip and of the Red-Dead canal. Through these two examples, this article analyzes the relationships between the Palestinian Authority and financial sponsors on the one hand, and the civil society on the other hand. It studies and compares how various actors define both water problems and solutions, and shows that the representations of the Israeli-Palestinian conflict and of water are co-constructed.